Self-Help Seeking for People Concerned About Their Thoughts and Behaviors Regarding Children During the COVID-19 Pandemic - Michael C. Seto; Kailey Roche; Jenny Coleman; Donald Findlater; Elizabeth J. Letourneau (Sexual Offending, 2025)
Concerns about the impacts of the COVID-19 pandemic on child sexual exploitation and abuse have been expressed by police and child protection organizations. However, there are limited data about how the pandemic may have caused changes in the help-seeking behavior of people who have concerns about their thoughts and behaviors regarding children. In this study, we examine helpline and webpage metrics from two organizations – Stop It Now! USA and Lucy Faithfull Foundation’s Stop It Now! UK and Ireland – providing resources about child sexual exploitation and abuse prevention, including self-help pages for people concerned about their sexual thoughts or behaviors involving children. Pages for self-help seekers were compared to pages for parents/caregivers and general audiences. Based on descriptive data, there was mixed evidence of an increased demand for self-help, with an increase in helpline inquiries and an increase in views for some but not all self-help pages. Webpage trends for self-help pages were not matched by similar trends for parent/caregiver or general information pages, suggesting the increase in demand was specific to self-help seeking. However, ANOVAs of both US and UK and Ireland webpage data did not result in a significant interaction effect between category (self-help, parent, or general) and time. While there were significant increases in self-help related helpline calls in the USA across time, all three types of helpline calls increased in the UK and Ireland. The implications of these data for self-help resources and perpetration prevention are discussed.